Early Inflammatory Response following Traumatic Brain Injury in Rabbits Using USPIO- and Gd-Enhanced MRI. (27th October 2016) - Ouyang, Lin; Zeng, Si; Zheng, Gang; Lu, Guang Ming
Abstract : Purpose . To monitor the inflammatory response (IR) following traumatic brain injury (TBI) before and after the rehabilitation of the blood-brain barrier (BBB) in rabbits using USPIO- and Gd-enhanced MRI. Materials and Methods . Twenty white big-eared rabbits with mild TBI (mTBI) were randomly and equally divided into four groups. Rabbits were sacrificed for the brain specimens immediately after the last MRI-monitoring. Sequences were tse-T1WI, tse-T2WI, Gd-T1WI, and USPIO-T1WI. Dynamical MRI presentations were evaluated and compared with pathological findings for each group. Results . Twenty-four hours after injury, all rabbits displayed high signal foci on T2WI, while only 55% lesions could be found on Gd-T1WI and none on USPIO-T1WI. The lesions were enhanced on Gd-T1WI in 100% subjects after 48 h and the enhancement sizes augmented to the largest after 72 h. At the time point of 72 h after TBI, 90% lesions were enhanced by USPIO. Five days after injury, 19 lesions showed decreased Gd-enhancement and one disappeared; however, USPIO-enhancement became larger than before. Pathological findings showed microglias slightly appeared in dense leukocytes at 48 h, but became the dominant inflammatory cells after five days. Conclusions . Dynamic IR following injury could be monitored by combination of Gd- and USPIO-MRI in mTBI rabbits.